A review on organophosphate flame retardants in indoor dust from China: Implications for human exposure. (December 2020) - Chen, Yixiang; Liu, Qiyuan; Ma, Jin; Yang, Shuhui; Wu, Yihang; An, Yanfei
Abstract: To investigate the status of organophosphate flame retardants (OPFRs) in indoor dust in China, published scientific studies were systematically collected and analyzed. The analysis revealed large variations among microenvironments, including offices (median: 14.59 μg/g) and e-waste workshops (median: 13.36 μg/g), with high levels of OPFRs contamination. Chlorinated organophosphate ester flame retardants (Cl-OPFRs) were the dominant OPFRs (52–75%) in most indoor dust samples; however, in e-waste workshops, aryl- and alkyl-OPFRs were the most abundant. As an alternative flame retardant to polybrominated diphenyl ethers (PBDEs), OPFRs concentrations have increased in recent years in indoor environments in China. Urban sources are of greatest concern: Shanghai (mean: 13.54 μg/g), Guangzhou (mean: 10.76 μg/g), and Beijing (mean: 9.37 μg/g) have high ΣOPFRs contamination levels in indoor dust. Compared to other countries, the OPFRs concentrations in indoor dust in all studied microenvironments from China (median: 8.81 μg/g) were low. The estimated daily intakes of ΣOPFRs by dust ingestion for adults and children were 2.12 and 11.06 ng/kg/body weight/day (average), respectively. Human exposure to OPFRs through the accidental intake of indoor dust does not pose a direct health risk to the Chinese population. However, indoor dust ingestion is an important route for human exposure to OPFRs. Highlights: OPFRs concentrations increased in indoor environments of China in recent years. OPFRs concentrations in indoor dust of offices and e-waste workshops were higher. Cl-OPFRs were the predominant components of OPFRs in indoor dust of China. Indoor dust ingestion is an important route for human exposure to OPFRs.